2020
DOI: 10.1109/access.2020.2979226
|View full text |Cite
|
Sign up to set email alerts
|

Spam Review Detection Using the Linguistic and Spammer Behavioral Methods

Abstract: Online reviews regarding different products or services have become the main source to determine public opinions. Consequently, manufacturers and sellers are extremely concerned with customer reviews as these have a direct impact on their businesses. Unfortunately, to gain profits or fame, spam reviews are written to promote or demote targeted products or services. This practice is known as review spamming. In recent years, the spam review detection problem has gained much attention from communities and resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…(3), it gives a value of almost zero when the distance goes beyond 10 (Figure 2). Thus, to solve this issue, the distances between the agents are projected to the range [1,4]. The G i component in Eq.…”
Section: A the Grasshopper Optimization Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…(3), it gives a value of almost zero when the distance goes beyond 10 (Figure 2). Thus, to solve this issue, the distances between the agents are projected to the range [1,4]. The G i component in Eq.…”
Section: A the Grasshopper Optimization Algorithmmentioning
confidence: 99%
“…The GOA algorithm starts by generating a random population Update the parameter c using Eq. (8); for each grasshopper in population Normalize the distances between grasshoppers in X d i to [1], [4]; Update x ∈ X d i by using Eq. (7); Adjust the boundaries for the current grasshopper in population; end for Update T if there is a better solution; iter = iter + 1; end while Return the best solution of T; grasshopper (solution) x d , d = 1, 2, .…”
Section: A the Grasshopper Optimization Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, collective behaviors of a group working together on several products can be difficult to identify the spam reviews. Most of the existing studies have identified spam reviews by utilizing the individual spammer behavioral features (Cao et al, 2019;Hussain et al, 2020;Rahman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%